Gestión administrativa de la fundación “Funduna” En La Ciudad De Babahoyo. - León Ramírez, Laura Lastenia (2022)
This case study was developed with the purpose of helping to identify the shortcomings of the different areas of the "Funduna" foundation of the city of Babahoyo, since administrative management is of the utmost importance to carry out institutional processes in an organized manner. This will help to favorably execute all the activities of the institution in a productive and efficient manner. In addition, this will allow a continuous improvement for the foundation and will allow generating competence in its officials, thus exploiting the capacities of the professionals who provide their services. in the aforementioned foundation. To carry out this research project, the survey of employees and interviews with officials in the administrative area through class questions were used as a technique for gathering information, this helped to better visualize the current situation of the organization and determine the latent problems and propose solutions that would considerably improve the development of the institution through administrative management.